FAKTOR PENYEBAB KETIDAKPATUHAN REMAJA PUTRI DALAM KONSUMSI TABLET TAMBAH DARAH - Siti Kistimbar; Yulianti Anwar; Farihah Indriani; Hermita Bus Umar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Adolescent girls are one of the groups at high risk for iron-deficiency anemia. Adolescent girls during puberty are particularly vulnerable to iron-deficiency anemia. This vulnerability is primarily due to increased iron requirements during periods of rapid growth, as well as regular blood loss through menstruation. The purpose of this study was to identify the factors contributing to non-compliance among adolescent girls regarding the consumption of iron supplements. The study design used in this research was cross-sectional. The study was conducted at a high school in Mamuju. The research was carried out in April 2025. The study sample consisted of 65 female students. Simple random sampling was used as the sampling technique. The research instrument used was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between knowledge (p-value: 0.000) and exposure to information (p-value: 0.025) with non-compliance in iron tablet consumption. It is recommended that female students proactively seek information regarding the benefits of iron tablets to reduce the risk of anemia among adolescents. Keywords: Information, Noncompliance, Knowledge